The Predation of Artemia Nauplii by the Larvae of the Amazon River Prawn, Macrobrachium amazonicum (Heller, 1862), is Affected by Prey Density, Time of Day, and Ontogenetic Development - Maciel, Cristiana R.; New, Michael B.; Valenti, Wagner Cotroni [UNESP] (Wiley-Blackwell, 2012)
The present study analyzed the effects of prey density, the time of day, and ontogenetic development on the predation of Artemia nauplii by the larvae of the Amazon river prawn, Macrobrachium amazonicum, as well as possible synergy among these factors. Larvae were raised in 120-L tanks with biological filter systems, and fed on recently hatched Artemia nauplii, using two feeding management protocols: (a) fed once per day at 2000 h (high density HD) and (b) half of the ration provided at 2000 h, complemented at 0800 h the following day by a replacement of the nauplii consumed up to a maximum of the full ration (low density with replacement LDWR). Each treatment consisted of six replicates. The consumption of nauplii was estimated prior to the feeding times. Consumption varied according to time of day, ontogenetic development, and feeding protocol. The larvae ingested more nauplii during the daytime at most developmental stages. Ingestion rates were similar during the day under both treatments, but at night the higher density of prey in the HD treatment caused a higher encounter rate and increased ingestion of nauplii by the larvae. Among the performance indicators only survival was greater in HD in comparison with LDWR; productivity and dry weight were similar. The results indicate a circadian trophic rhythm in M. amazonicum, with the encounter rate being an important mechanism for the capture of prey during the night. A second mechanism probably the visual system aids the perception of prey during the daytime. Based on these results, we suggest that feeding captive Amazon river prawn larvae only once a day would be appropriate and economically beneficial. Further work is necessary to determine the most effective time that this single feed should be applied.